2019
DOI: 10.1038/s42003-019-0514-3
|View full text |Cite
|
Sign up to set email alerts
|

Myosin-II mediated traction forces evoke localized Piezo1-dependent Ca2+ flickers

Abstract: Piezo channels transduce mechanical stimuli into electrical and chemical signals to powerfully influence development, tissue homeostasis, and regeneration. Studies on Piezo1 have largely focused on transduction of “outside-in” mechanical forces, and its response to internal, cell-generated forces remains poorly understood. Here, using measurements of endogenous Piezo1 activity and traction forces in native cellular conditions, we show that cellular traction forces generate spatially-restricted Piezo1-mediated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

33
209
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(242 citation statements)
references
References 77 publications
(112 reference statements)
33
209
0
Order By: Relevance
“…Biophysical studies have shown that membrane bilayer tension changes can directly activate Piezo1 ion channels and the regulation of Piezo1's function has been attributed to the regulation of localized lipid bilayer tension changes 12,13 . This is supported by biophysical studies that Piezo1 is sensitive to specific lipid types 14 and the observations that Piezo1 is diffusively localized in plasma membranes of many cell lines with very few interaction partners identified 4,13,15,16 . However, an open question In the regulation of Piezo1 is the intimate involvement of the integrin-linked actin cytoskeleton in Piezo1's functions 17 .…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…Biophysical studies have shown that membrane bilayer tension changes can directly activate Piezo1 ion channels and the regulation of Piezo1's function has been attributed to the regulation of localized lipid bilayer tension changes 12,13 . This is supported by biophysical studies that Piezo1 is sensitive to specific lipid types 14 and the observations that Piezo1 is diffusively localized in plasma membranes of many cell lines with very few interaction partners identified 4,13,15,16 . However, an open question In the regulation of Piezo1 is the intimate involvement of the integrin-linked actin cytoskeleton in Piezo1's functions 17 .…”
Section: Introductionmentioning
confidence: 60%
“…Since the discovery of Piezo1's role as a mechanosensitive ion channel in eukaryotic cells, the regulation mechanism of Piezo1's function in the various physiological activities of cells has been under heavy investigation 8,9 . The current model of Piezo1's physiological function assumes that it is diffusive in the plasma membrane and is activated locally through membrane bilayer tension or curvature changes that occur through cytoskeletal-dependent mechanical events 13,15,17,40,42 . In these studies, we find that the involvement of Piezo1 in cell spreading on fibronectin is lost with cell transformation and also with spreading on collagen.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the activity of the downstream signaling pathways that govern the microgravity-induced cytoskeletal changes are significantly impaired and are at least in part due to the microgravitytriggered inhibition of FAK and/or RhoA signaling (Higashibata et al, 2006;Li et al, 2009;Tan et al, 2018). Furthermore, recent data suggest that changes to the cytoskeleton may also impact signaling via mechanically activated ion channels and contacts in response to both cell-generated (Nourse and Pathak, 2017;Ellefsen et al, 2019) and externally applied mechanical inputs (Bavi et al, 2019). Thus, downstream signaling of the numerous mechanotransduction pathways depend on the concerted interaction of the cytoskeleton, cell adhesion molecules, and force sensing proteins, including mechanically activated ion channels.…”
Section: The Impact Of Microgravity Of Cell Cytoskeletonmentioning
confidence: 99%
“…Interestingly, Piezo1 channels seem to form clusters when heterologously expressed in mammalian cells and this clustering has been proposed to play a role in concerted gating transitions such as collective loss of inactivation ( 28-30 ). While it is currently unclear whether endogenous Piezo1 form native clusters in vivo, these results together suggest that the gating properties of Piezo channels can be modulated by the local channel density at the plasma membrane.…”
Section: Discussionmentioning
confidence: 99%